2021
DOI: 10.7759/cureus.13764
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Cardiac Death and Sudden Cardiac Arrest in Patients with Human Immunodeficiency Virus: A Systematic Review

Abstract: The importance of this review lies in its study of the risk of sudden cardiac death (SCD) and sudden cardiac arrest (SCA) in people living with the human immunodeficiency virus (PLWH). To the best of our knowledge, this is the first review investigating the effect of the human immunodeficiency virus (HIV) on SCD and SCA. The review's objective was to determine the risk of SCD and SCA in PLWH. To do this, the electronic databases Ovid MEDLINE, EMBASE, Cochrane Central, Scopus, and Google Scholar were systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The incidence rate of SCD among PLWH was shown to be 2-4 fold higher than those without HIV infection. [73] Recent data obtained from cardiac magnetic resonance imaging (CMR) and autopsy have shown that diffuse myocardial fibrosis, a risk factor for SCD, is prevalent among PLWH. [74,75] Other possible factors which contribute to the increased risk of SCD among PLWH include: (i) high prevalence of coronary artery disease [76], (ii) concomitant illicit drug use [76,77], and (iii) QT prolongation due to medications and possibly from a direct effect of HIV infection [77].…”
Section: Human Immunodeficiency Virus (Hiv) Infection and Scd Riskmentioning
confidence: 99%
“…The incidence rate of SCD among PLWH was shown to be 2-4 fold higher than those without HIV infection. [73] Recent data obtained from cardiac magnetic resonance imaging (CMR) and autopsy have shown that diffuse myocardial fibrosis, a risk factor for SCD, is prevalent among PLWH. [74,75] Other possible factors which contribute to the increased risk of SCD among PLWH include: (i) high prevalence of coronary artery disease [76], (ii) concomitant illicit drug use [76,77], and (iii) QT prolongation due to medications and possibly from a direct effect of HIV infection [77].…”
Section: Human Immunodeficiency Virus (Hiv) Infection and Scd Riskmentioning
confidence: 99%
“…The incidence of sudden cardiac death (SCD) in people living with HIV infection (PLWH), especially those with inadequate viral suppression, is significantly higher than that of the general population [1][2][3][4][5][6]. The risk factors that contribute to this include sex, vascular aging, hyperactive sympathetic and immune systems, inflammation, cardiac ischemia and fibrosis, and illicit and prescription drug use [1,[5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…4 Initially the introduction of protease inhibitors (PIs) was associated with hyperlipidemia and consequently even a higher risk of major cardiovascular events. 5,6 However, the risk of CVD, including acute myocardial infarction, 7 sudden cardiac death, 8 stroke, 9,10 heart failure 11 and peripheral arterial disease, 12 remains signifi cantly higher than in the general population, and cannot be explained by PIs alone. 13 Some studies show a higher prevalence of cardiovascular risk factors, such as hypertension, cigarette smoking, 14 metabolic syndrom, 15 diabetes, 16 dyslipidemia, 17 and depression 18 in HIV-infected individuals compared with uninfected individuals.…”
Section: Introductionmentioning
confidence: 99%